Jenis Dan Kelimpahan Makrozoobentos Di Perairan Sungai Salukaia Kecamatan Pamona Barat Kabupaten Poso - Muhdin, Nining Kasim; Torodjo, Sandra (Jurnal Biologi Babasal, 2023)
Abstract: The results of the survey determine the types and describe the benthic macrofauna in the Salukai River, West Pamona District. This monitoring is carried out at three stations, namely Station I upstream, Station II in the middle of the river, and Station III downstream. The station guarantee test was carried out using purposive inspection, especially the location of the test location using the survey method with a flow length of 7 km. The exploration results revealed six species of benthic macrofauna: Brotia testudinaria, Lymnaea rubiginosa, Rhyacophila acotilova, Ophiogomphus rupiussulensis, Pila ampullacea, and Chironomus pullosus. From the survey results, a total of 43 individuals from four species at Station I were confirmed, a total of 74 individuals from five species at Station II, and a total of seven species from one species at Station III. In general, the relative richness of benthic macrofauna: KR = 33,586 individuals at station I, KR = 32,182 individuals at station II, and KR = 0.1 individuals at station III.